Fragmented QRS complexes are a marker of myocardial fibrosis in hypertensive heart disease - Lütfü Bekar; Muzaffer Katar; Mücahit Yetim; Oğuzhan Çelik; Hakan Kilci; Orhan Önalan (KARE Publishing, 2016)
Objective: Carboxy-terminal propeptide of type 1 procollagen (PICP) is a marker of extracellular collagen synthesis. Fragmented QRS (fQRS) on a 12-lead electrocardiogram (ECG) has been demonstrated as a marker of myocardial fibrosis. The present objective was to investigate the association between serum PICP concentration and presence of fQRS on ECG in hypertensive patients. Methods: Consecutive patients with previously or newly diagnosed hypertension were included. fQRS was defined as the presence of additional R-wave (R'), or notching of R- or S-waves, or the presence of fragmentation in 2 contiguous ECG leads. Serum PICP levels were measured by ELISA method. Results: The study group consisted of 90 hypertensive patients (74% females, with a mean age of 54.7+-8.5 years). Of these patients, 47 (52.2%) had fQRS on ECG. Age (p=0.121) and gender distribution (p=0.625) were similar in patients with or without fQRS. Receiver operating characteristic curve analysis yielded a strong predictive ability of PICP levels for the presence of fQRS (area under the curve: 0.850; 95% CI: 0.772-0.929; p<0.0001). In multivariate logistic regression analysis, PICP levels were strongly and independently associated with the presence of fQRS (OR: 1.938; 95% CI: 1.398-2.688). Conclusion: Serum PICP level is a strong and independent predictor of fQRS. Discriminative performance of serum PICP levels for the presence of fQRS is high. The present results are the first to demonstrate that fQRS may indicate myocardial fibrosis in patients with hypertension.